Case 904-12-JP/19 (pregnancy care denial and obstetric violencen) - Guapizaca Jiménez, Erick Fabián (2021)
This jurisprudential analysis examines judgment 904-12-JP/ 19 (denial to care for pregnancy and obstetric violence), delivered by Judge Ramiro Ávila Santamaría, issued by the Constitutional Court of Ecuador. The failure was handed down within the framework of the review of a sentence of a protection writ presented by a woman who had not been adequately cared for by the maternity system of the Ecuadorian Social Security Institute and who as a result suffered acts of obstetric violence and violations of their rights to health and to social security. In a first section, the investigative work describes and analyzes the constitutional process of selection and review of judgments of jurisdictional writs, as well as the scope and nature of the judgments of binding jurisprudence . In a second section, the peculiar method of the sentence is studied in detail to introduce the problem of deficient health care for pregnant women. Likewise, the reasoning of the judge regarding the definition of the content of the rights that are declared violated is critically examined: health and social security; The unprecedented incorporation of the concept of obstetric violence is studied and a comment is provided regarding the reparations ordered in the case.